Incidence of Traumatic Stomatitis with Intensity of Fixed Orthodontic Patient Control in Students of the Faculty of Medicine, Wijaya Kusuma University Surabaya - Almaidah Safitri; Wahyuni Dyah Parmasari (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Background. Traumatic stomatitis is inflammation of the oral mucosa caused by the use of orthodontic appliances, it can be due to discomfort when using orthodontic appliances, allergies to orthodontic appliance materials, pinched or punctured oral mucosa.Method. The design of this research is a cross sectional and analytic observation. With the population and sample of this study, students of the Faculty of Medicine, Wijaya Kusuma University, Surabaya who performed fixed orthodontic treatment in the period May-June 2022.Conclusion. The data analysis used in this study was Fisher's exact test. The results showed that there was significant relationship between the intensity of control and the incidence of traumatic stomatitis in fixed orthodontic users at the Faculty of Medicine, Wijaya Kusuma University, Surabaya. The intensity of routine control can add information about how to maintain oral hygiene, as well as the use of oral hygiene aids that may help prevent traumatic stomatitis.